Cost-effectiveness of Simple Insulin Infusion Devices Compared to Multiple Daily Injections in Uncontrolled Type 2 Diabetics in the United States Based on a Simulation Model - Peter Wahlqvist; Jay Warner; Robert Morlock (Journal of Health Economics and Outcomes Research)
**Background:** As type 2 diabetes (T2D) progresses, administering basal and bolus insulin through multiple daily injections (MDI) is often required to achieve target control, although many people fail to achieve target levels. Continuous subcutaneous insulin infusion (CSII) treatment with traditional pumps has proven effective in this population, but use remains limited in T2D due to CSII cost and complexity. A new class of simple insulin infusion devices have been developed which are simpler to use and less expensive. This paper assesses at what price one such simple insulin infusion device, PAQ® (Cequr SA, Switzerland), may be cost-effective compared to MDI in people with T2D not in glycemic control in the United States.